Comparison of caudal bupivacaine and dexmedetomidine with caudal bupivacaine and intravenous dexmedetomidine for postoperative analgesia in children: A randomized controlled trial - Kuldeep Singh; Jeetendra Bajaj; Sapna Bathla; Khushboo Mehta (Journal of Anaesthesiology Clinical Pharmacology, 2025)
Background and Aims: Caudal block is a part of multimodal analgesic regimen to alleviate pain in pediatric patients undergoing variety of surgeries. This study compares the effectiveness of caudal versus intravenous dexmedetomidine as an additive to caudal bupivacaine for prolonging analgesia in children posted for elective lower abdominal surgeries. The level of sedation and hemodynamic effects through both routes were also compared. Material and Methods: Ninety-six children (aged 1–8 years) of either gender scheduled for elective lower abdominal and pelvic surgeries were prospectively enrolled and randomized into two groups of 48 each: Group A (caudal bupivacaine + caudal dexmedetomidine) and Group B (caudal bupivacaine + intravenous dexmedetomidine). The postoperative pain was monitored using the Face, Legs, Activity, Cry, Consolability (FLACC) scale, and sedation was assessed using the Ramsay sedation scale (RSS). Results: The degree of analgesia was comparable in both groups in the initial hours after surgery. Significantly higher FLACC scores were seen in Group B at 8 h (P- 0.016), 12 h (P < 0.001), and 16 h (P < 0.001), with 89.58% patients needing two rescue analgesic doses. RSS was higher in Gr=oup A till 12 h postsurgery. Conclusion: Caudal dexmedetomidine with bupivacaine provides improved analgesia after 8 h of surgery in comparison to caudal bupivacaine with intravenous dexmedetomidine in children undergoing lower abdominal surgeries.